Variasi Marga Plumeria berdasarkan Karakter Morfologi Pollen di Wilayah Purwokerto Banyumas Jawa Tengah - Sukarsa Sukarsa; wiwik herawati (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2021)
The Plumeria clan is a member of the Apocynaceae family and has variations in each type. This study aims to determine the variation in morphological characters of the Plumeria genus pollen in the Purwokerto region. The results showed that the pollen morphology of 6 samples, namely Plumeira rubra, Plumeira rubra f angutifolia, Plumeira rubra f frangifani, Plumeira obtusu, Plumeira alba and Plumeira pudica have similarities in the type of aperture, namely tricolpate type and psilate type ornamentation. While the comparative P / E index The mean length of the polar axis (P) and the diameter of the equatorial plane (E) P. rubra, P. rubra F frangifani and P obtusus have the form of Oblate Spheroidal type pollen with P / E index 0.92 - 0.94 while Plumeira alba and Plumeira pudica Suboblate pollen form with P / E index 0.82 - 0.85